Virtual-freezing fluorescence imaging flow cytometry - Hideharu Mikami (Nature Portfolio, 2020)
High throughput imaging flow cytometry suffers from trade-offs between throughput, sensitivity and spatial resolution. Here the authors introduce a method to virtually freeze cells in the image acquisition window to enable 1000 times longer signal integration time and improve signal-to-noise ratio.